Active control of stick-slip oscillations in oil-well drilling systems - Cruz Neto, Helio Jacinto da (2023)
Rotary drilling systems are subjected to harmful interactions between the drilling structure, borehole and rock formation, leading to torsional stick-slip vibrations that can decrease drilling efficiency and cause drill string component failures. A proper way to reduce these detrimental failures is to design an active controller that efficiently mitigates vibrations with the constraint of using the limited amount of real-time data available in field operations. In this context, this thesis proposes two novel control techniques relying only on simple linear combinations of measured signals to mitigate drill string torsional vibrations and improve drilling performance. Since the measured signals are of paramount importance for the effectiveness of the proposed techniques, this work also investigates which signals are relevant for feedback with the aim of ensuring asymptotic stability. The first proposed control technique relies on a work developed by the author during his master\'s degree, and consists of determining the control gain of an output feedback controller (OSOF) such that its performance is as close as possible to that of a full state feedback controller (LQR). The second proposed control technique derives from the negative damping coefficient concept developed in this thesis, and aims to enlarge the limits of drill string safe operation by minimizing the value of the negative damping coefficient for which the operating point is asymptotically stable. The proposed controllers are applied to a representative drill string torsional dynamics model, modeled using the finite element method with non-regularized dry friction. The model developed contemplates the particular aspects regarding the application of the proposed controllers, such as the reformulation of the equations of motion as a stabilization problem and the addition of an integral action. Simulations reveal that the proposed controllers perform better than an optimized PI controller both in the case of known parameters and in the presence of uncertainties. Furthermore, sensitivity analyses indicate a seeming global stability of the closed-loop system equipped with one of the proposed controllers, in addition to very low sensitivity of performance with respect to parameter variations. Results motivate further investigations of the apparent global stability provided by the proposed controller and practical implementation of the developed strategies.